2021
DOI: 10.21147/j.issn.1000-9604.2021.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of cell heterogeneity and evolutionary trajectory in ulcerative colitis-associated colon cancer revealed by single-cell RNA sequencing

Abstract: Objective The goal of this study was to get preliminary insight on the intra-tumor heterogeneity in colitis-associated cancer (CAC) and to reveal a potential evolutionary trajectory from ulcerative colitis (UC) to CAC at the single-cell level. Methods Fresh samples of tumor tissues and adjacent UC tissues from a CAC patient with pT3N1M0 stage cancer were examined by single-cell RNA sequencing (scRNA-seq). Data from The Cancer Genome Atlas (TCGA) and The Human Protein At… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Moreover, studies have shown that anti-inflammatory drugs can reshape the tumor immune environment and enhance the immune blocking effect ( Pelly et al, 2021 ). Clinical studies have found that there may be a correlation between ulcerative colitis and colon cancer and that inflammatory cells are present in tumor biopsy samples ( Wang et al, 2021 ). The clinical utility of inflammation-related biomarkers in routine blood tests has been reported in a variety of cancers, and Yamamoto, T. summarizes the prognostic impact of each inflammation-related marker on CRC ( Yamamoto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that anti-inflammatory drugs can reshape the tumor immune environment and enhance the immune blocking effect ( Pelly et al, 2021 ). Clinical studies have found that there may be a correlation between ulcerative colitis and colon cancer and that inflammatory cells are present in tumor biopsy samples ( Wang et al, 2021 ). The clinical utility of inflammation-related biomarkers in routine blood tests has been reported in a variety of cancers, and Yamamoto, T. summarizes the prognostic impact of each inflammation-related marker on CRC ( Yamamoto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cells, compared to fibroblasts isolated from normal adjacent tissues had 76 differentially expressed genes (DEG), 5 of which ( BGN , RCN3 , TAGLN , MYL9 , and TPM2 ) were associated with poorer prognosis in the TCGA database [ 68 ]. Wang et al performed droplet-based scRNA-seq on cancerous and adjacent non-malignant inflamed tissue from a patient with ulcerative colitis-associated colon cancer [ 69 ]. They analyzed 2250 cells from tumor tissues and 2527 cells from non-malignant tissues, and classified them into cell types (myeloid cells, T cells, B cells, fibroblasts, endothelial cells, and epithelial cells) based on their transcriptional activity and further clustered them using the t-SNE method.…”
Section: Bulk Vs Single-cell Experiments In Colorectal Adenomas and A...mentioning
confidence: 99%
“…Advances in single-cell RNA sequencing (scRNA-seq) have revolutionized the ability to further investigate the transcriptional status of individual cells. ScRNA-seq has been successfully applied to identify cell types and understand complex subsets in various cancers, including lung ( 1 ), breast ( 2 ) and colon cancer ( 3 ). By contrast, single cells are challenging to recover entirely from certain tissues, such as brain tissue ( 4 ), and certain single cells, such as adipocytes ( 5 ), are incompatible with the droplet-based single-cell approach.…”
Section: Introductionmentioning
confidence: 99%